The Effect Of Various Ash To Growth and Yield Of Radish On Peatsoil - wahyu fitriani, wahyu fitriani (Jurnal Sains Pertanian Equator, 2019)
This study aims to determine how much response the giving of various ash to the growth and yield of radish on peat soil. This study was done in the college of agriculture garden of Tanjungpura University Pontianak, the study started on September 5th- October 28th, 2018 The design used in this study was a completely randomized design (CRD), consisting of 5 treatments that is, oil palm empty bunches ash (a1), wood ash (a2), corn stover ash (a3), coconut husk ash (a4) and rice husk ash (a5) repeated 5 replications and each replication consisted of 4 samples. The variables observed were the number of leaves, fresh weight of plants, fresh weight of tubers, tuber length, tuber diameter, plant dry weight. The application of wood ash with a dose of 416 g / 8 kg of soil gave the best response on the growth and yield of radish that is number of leaves, fresh weight pf plants, fresh weight of tubers, tuber length, tuber diameter, and plant dry weight compared to the application of oil palm empty bunches ash, coconut husk ash, corn stover ash and rice husk ash.